The Uptake and Effectiveness of a Multidisciplinary Online Program for Managing Chronic Pain before and During the COVID-19 Pandemic. Issue 9 (21st March 2022) - Shiner, Christine T; Gardner, Tania; Haskelberg, Hila; Li, Ian; Faux, Steven G; Millard, Michael; Mahoney, Alison E J
Abstract: Objectives: Societal and health system pressures associated with the coronavirus disease 2019 (COVID-19) pandemic exacerbated the burden of chronic pain and limited access to pain management services for many. Online multidisciplinary pain programs offer an effective and scalable treatment option, but have not been evaluated within the context of COVID-19. This study aimed to investigate the uptake and effectiveness of the Reboot Online chronic pain program before and during the first year of the COVID-19 pandemic. Methods: Retrospective cohort analyses were conducted on routine service users of the Reboot Online program, comparing those who commenced the program during the COVID-19 pandemic (March 2020–March 2021), to those prior to the pandemic (April 2017–March 2020). Outcomes included the number of course registrations; commencements; completion rates; and measures of pain severity, interference, self-efficacy, pain-related disability, and distress. Results: Data from 2, 585 course users were included (n = 1138 pre-COVID-19 and n = 1, 447 during-COVID-19). There was a 287% increase in monthly course registrations during COVID-19, relative to previously. Users were younger, and more likely to reside in a metropolitan area during COVID-19, but initial symptom severity was comparable. Course adherence and effectiveness were similar before and during COVID-19, with moderate effect size improvements in clinical outcomes post-treatment ( g = 0.23–0.55). Discussion: Uptake of an online chronic pain management program substantially increased during the COVID-19 pandemic. Program adherence and effectiveness were similar pre- and during-COVID. These findings support the effectiveness and scalability of online chronic pain management programs to meet increasing demand.